Konstruksi Hukum Dalam Rangka Penguatan LPD Sebagai Lembaga Keuangan Milik Desa Adat di Provinsi Bali - Ida Bagus Alit Yogamaheswara; I Made Dwija Suastana; Ni Luh Made Elida Rani; Agung Rio Swandisara; Kadek Virra Melyana Dewi (Fakultas Hukum, Universitas Warmadewa, 2023)
LPD as an institution that has the authority to collect public funds for the welfare of traditional villages has many problems today. The root of the problem can be seen from: 1). The void of norms that explains LPD as a legal entity within the framework of legal norms but has operated like other financial institutions; 2). The lack of clarity in the supervision of the LPD has resulted in many problems and even cases of corruption. This void of legal norms creates doubts from the perspective of criminal law with customary law because the LPD is predicted to be an institution belonging to the traditional village but the traditional village does not have adequate tools to solve the problems that exist within the LPD, privately or publicly. Meanwhile, from a criminal law perspective, the Prosecutors and Police consider that the misappropriation of funds by the LPD is a criminal act of corruption and both cannot provide a solution to the problems desired by the community. This paper was written with the aim of providing a new understanding in legal standing of the LPD using the legal construction reasoning method in order to strengthen the status of the LPD as an institution under the customary village using the main legal sources where the expected result is that armed with an understanding of the legal construction, it can be used as a reference for traditional practitioners and law enforcers will be able to formulate good problem solving and fulfill a sense of justice in society. The method used for this research is normative legal research with primary, secondary and tertiary legal materials where what is being researched is to answer the void of norms in the LPD’s position as legal subjects where with clear LPD legal standing there will be a legal discovery to make it easier for the government to formulate regulations.from the authority, supervision and law that is applied in the event of a legal problem.